Screening Sarcoidosis Patients for Occult Disease - Judson, Marc A. (Seminars in Respiratory and Critical Care Medicine, 2020)
As sarcoidosis may involve any organ, sarcoidosis patients should be evaluated for occult disease. Screening for some organ involvement may not be warranted if it is unlikely to cause symptoms, organ dysfunction, or affect clinical outcome. Even organ involvement that affects clinical outcome does not necessarily require screening if early detection fails to change the patient's quality of life or prognosis. On the other hand, early detection of some forms of sarcoidosis may improve outcomes and survival. This manuscript describes the approach to screening sarcoidosis patients for previously undetected disease. Screening for sarcoidosis should commence with a meticulous medical history and physical examination. Many sarcoidosis patients present with physical signs or symptoms of sarcoidosis that have not been recognized as manifestations of the disease. Detection of sarcoidosis in these instances depends on the clinician's familiarity with the varied clinical presentations of sarcoidosis. In addition, sarcoidosis patients may present with symptoms or signs that are not related to specific organ involvement that have been described as parasarcoidosis syndromes. It is conjectured that parasarcoidosis syndromes result from systemic release of inflammatory mediators from the sarcoidosis granuloma. Certain forms of sarcoidosis may cause permanent and serious problems that can be prevented if they are detected early in the course of their disease. These include (1) ocular involvement that may lead to permanent vision impairment; (2) vitamin D dysregulation that may lead to hypercalcemia, nephrolithiasis, and permanent kidney injury; and (3) cardiac sarcoidosis that may lead to a cardiomyopathy, ventricular arrhythmias, heart block, and sudden death. Screening for these forms of organ involvement requires detailed screening approaches.
Keywords: sarcoidosis; screening; symptoms; cardiac; vitamin D